Peran Kepemimpinan Inovatif Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan Sekolah Dasar: The Role of Innovative Leadership of School Principals in Improving the Quality of Elementary Education - Hidayat, Syarif; Dimyati, Didim (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
This research adopts a qualitative approach, which is a research method that aims to observe research objects naturally and directly. In the context of this research, researchers act as the main instrument in collecting data and information related to the research object being investigated. The location of this research is SD Al-falah Cicalengka Bandung. The address is Jl. Captain Sangun No. 6 Rt. 01 Rw. 03, Tenjolaya, District. Cicalengka, Kab. Bandung Province West Java. The research instruments applied in this research are interviews and observations to find data and facts related to the role of innovative school principal leadership in improving the quality of education. At this stage, the principal of SD Al-Falah Cicalengka Bandung carries out several things, including: (1) Holding a meeting with all elements of the teaching staff at the school to formulate and determine the school's annual program which will be implemented at the beginning of the learning year. (2) Formulate all forms of facility needs required by the school based on each time period. (3) Holding a meeting at the beginning of the year regarding the implementation of the learning curriculum. In accordance with the statement of Bapa Syarif Hidayat, S.Pd.I as Principal of SD Al-falah Cicalengka Bandung "In terms of planning at school, I involve teachers in deliberations at the beginning of the year to discuss the school program for the next year."